2019
DOI: 10.1097/pas.0000000000001342
|View full text |Cite
|
Sign up to set email alerts
|

RELA Fusion in Supratentorial Extraventricular Ependymomas: A Morphologic, Immunohistochemical, and Molecular Study of 43 Cases

Abstract: Supratentorial extraventricular ependymomas (STEEs) are relatively rare ependymomas, and their pathologic and genetic characteristics are still poorly understood. The aim of this study was to determine the histologic, immunohistochemical, and RELA fusion features, as well as to clarify in more detail the clinical courses of STEEs. Data from a total of 43 patients with STEEs was analyzed retrospectively. The status of RELA fusion was evaluated using fluorescence in situ hybridization. The expression levels of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…RELA fusion-positive ependymoma has been considered as a novel entity according to the 2016 WHO classification of CNS tumors (14). Previous studies depicted that incidence of C11orf95-RELA fusions in STE ranging from 65.1 to 70% (15)(16)(17). However, the incidence of C11orf95-RELA fusions in CEs has rarely been investigated before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RELA fusion-positive ependymoma has been considered as a novel entity according to the 2016 WHO classification of CNS tumors (14). Previous studies depicted that incidence of C11orf95-RELA fusions in STE ranging from 65.1 to 70% (15)(16)(17). However, the incidence of C11orf95-RELA fusions in CEs has rarely been investigated before.…”
Section: Discussionmentioning
confidence: 99%
“…Matsumoto et al (11) found all CEs (5/5, 100%) had RELA fusions in their study. RELA fusion positive had been considered as a negative prognostic factor in ependymomas (16). However, Figarella-Branger et al (18) and Lillard et al (17) did not find that RELA fusion-positive STE had a poorer outcome; they hold GTR or near total resection (NTR) may overcome the deleterious effects of RELA fusion on survival (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Parker et al reported that the fusion genes resulted from clustered genomic rearrangements occurring in localized genomic regions, known as chromothripsis, at chromosome 11q12.1–11q13.3, and that the fusion proteins led to NF‐κB pathway activation with nuclear accumulation of p65/RelA (4). In addition, L1CAM, which was originally identified as a neural adhesion molecule essential for axonogenesis (9), was reported to be overexpressed in ST ependymomas with C11orf95 ‐ RELA (4,10,11), suggesting that L1CAM is a target of aberrant signaling of the fusion proteins (4). Overexpression of both p65/RelA and L1CAM is identifiable by immunohistochemistry (4,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the outcomes of patients with C11orf95-RELA fusion-positive ependymoma are worse than those of patients with the other two subtypes (Pajtler et al 2015;Malgulwar et al 2018;Wang et al 2019). Malgulwar et al (2018) and Wang et al (2019) found that L1CAM was consistent with the RELA fusion gene by more than 80%. In our study, amazingly, the PFS and OS of all patients were analyzed by Kaplan-Meier and Cox analyses, which revealed no difference between patients with L1CAM positivity and patients with L1CAM negativity (P > 0.05; Tables 2 and 3).…”
Section: Figmentioning
confidence: 99%
“…The reason for this inconsistent result might be the poor consistency of the application of L1CAM alone in the detection of the C11orf95-RELA fusion gene when we analyzed the data from our study and the recent literature. Several studies have suggested that markers such as P65 could also be included in tests to assess the presence of the C11orf95-RELA fusion gene (Gessi et al 2019;Wang et al 2019). In addition, although the presence of the RELA fusion gene is associated with poor outcomes, the difference might not be significant.…”
Section: Figmentioning
confidence: 99%